Trend and high risk clusters for the occurrence of congenital anomalies in the State of Mato Grosso, Brazil (2008-2019) - Bruna Rayeli Groth; Eliziani Gonçalves da Silva; Camila Beatriz Alves da Rocha; Bruna Hinnah Borges Martins de Freitas; Rafaela Benevides Ferreira Machado; Elena Alves Benevides Ferreira; Lúbia Maieles Gomes Machado; Emerson Soares dos Santos; Iara Denise Endruweit Battisti; Silvana Margarida Benevides Ferreira (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to analyze the spatiotemporal dynamics of the prevalence of congenital anomalies in in cities of Mato Grosso (MT), in the Mid-West of Brazil, from 2008 to 2019. Methods: an ecological study of cases in MT during the period from 2008 to 2019. The Annual Percent Change (APC) of the coefficients was used in the tendency analysis, through Prais-Winsten regression and the identification of high risk clusters. Results: the congenital malformation rate in the State was 6.52 per 1,000 live births, demonstrating a stationary tendency (APC-1.02; 95%CI= -2.93-0.93). Most congenital anomalies showed a stationary tendency, except for those of the cardiovascular system (APC=13.58; 95%CI= 3.60-24.52). Newborns with an Apgar score of ≤ 7 at the first and fifth minutes of life showed an increased tendency (APC=2.30; 95%CI=0.05-4.60 and APC=4.15; 95%CI= 1.52-6.65, respectively). The spatial distribution was heterogeneous, with the highest average rates of cases in the West, Central North, and South health macro-regions. The spatiotemporal scan identified three high risk clusters between 2015 and 2019, with a relative risk (RR) up to five times higher for anomalies. Conclusion: congenital anomalies in MT exhibited a heterogeneous dynamic with specific high risk areas, and their increasing tendency among maternal and neonatal factors highlights the need for regional prevention and control strategies.